Stakeholder management practices found in landlord seaport authorities in Flanders: an inside-out perspective. (2015) - Aerts, Geoffrey; Dooms, Michaël; Haezendonck, Elvira
This paper offers an analysis of stakeholder management conducted by port authorities. Drawing from several organisation-centric stakeholder management theories, we study the conceptualisation and the identification of stakeholders, as well as the application of stakeholder management, as executed by port authorities. By analysing the opinions of middle management, we examine whether daily stakeholder management reflects stakeholder theory findings, emphasising the importance of attribute-based stakeholder conceptualisation, identification, and stakeholder management strategies. We also conduct a comparative analysis, assessing the quality of the stakeholder management practice in several seaports located in the Rhine-Scheldt Delta. The results show that actual stakeholder management practices, found at several port authorities, convey moderate resemblance to the methods and theoretical findings presented in academic stakeholder management literature.